Murder on the home front [videorecording (DVD)] - Sax, Geoffrey; Merchant, Tamzin; Kennedy, Patrick, 1977-
Set during the London Blitz of 1940, here is a vibrant, original crime drama. This is a world where people live life in the moment. It is also a world where criminals can use the blackout and devastation to hide their darkest activities. As the Luftwaffe drop their bombs, below people are literally getting away with murder.